A century of motorisation in urban and rural contexts: paths of motorisation in German cities - Scheiner, Joachim (ERDKUNDE, 2012)
Historical trends in motorisation have been intensively studied by transport historians. However, this is not true for the spatial aspects of these trends. It is well-known that the level of motorisation today is considerably lower in cities than in suburban and rural areas. However, this has not always been the case. The paper studies spatial structures in motorisation for German cities over the period 1907 to 2008. A typology is developed including 80 cities according to their motorisation trends over the period 1938 to 2008. The results show characteristic paths of motorisation. It also becomes apparent that motorisation started in the cities, and the countryside ‘overtook’ the cities not before the 1960s in terms of motorisation levels.